Análise da confiabilidade de equipamentos e métodos para medir o movimento de flexão anterior da coluna lombar - Vieira, Edgar Ramos (Universidade Federal de São Carlos, 2002)
Current high incidence of low back pain represents high costs to patients, industries, health insurance companies and government. Moreover, it causes loss in life quality of suffers. Lumbar flexion movement is critical to the development and aggravation of low back pain. Thus, quantification of this movement is important to the prevention and treatment of these disorders. Therefore, the purposes of this research were: design two new methods to quantify lumbar flexion movement, improve electrogoniometer interfaces, and assess the reliability of three devices and methods to measure the studied movement. In order to achieve these objectives, three studies were designed. Study 1 has compared the measurements from an electrogoniometer fixed by Attachment Ducts (ADs), with those from another electrogoniometer without ADs, and the measurements of both electrogoniometers with those from a high precision goniometer. Study 2 has compared both conditions studied previously, when the electrogoniometers were fixed in parallel on lumbar muscles of 14 subjects. Study 3 presented the Perpendicular Markers Photometric Technique (PMPT) and the Distanciometer, both designed for this study. Furthermore, this study analyzed the reliability of the PMPT, fleximeters (usually known as inclinometers), and Distanciometer, when compared to the measurements of lumbar flexion movement of 25 subjects performed by an electrogoniometer. Results indicated that electrogoniometers are precise equipment, ADs did not influence measurements and provided a more specific definition of the region to be assessed by electrogoniometers, and high reliability was found for both PMPT and Distanciometer, but not for the fleximeters used in this study.
Keywords: Fisioterapia; Confiabilidade; Eletrogoniômetro; Flexímetro; Flexão lombar; Movimento; Reliability; Electrogoniometer; Fleximeter; Movement; Lumbar flexion; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL